“Furnace-smoke ... wrapt him round”: Industrial Hinduism and Global Empire in The Curse of Kehama and Sir Thomas More - DeFalco Lamperez, Joseph (Romanticism on the Net, 2017)
My essay claims that Robert Southey uses Hinduism to fashion a poetics of Romantic-era technology in The Curse of Kehama (1810). In his neglected Sir Thomas More; or, Colloquies on the Progress and Prospects of Society (1829), Southey compares the manufacturing system to Indian theology and ritual, a metaphor that relativizes religion and technology while implying that the Industrial Revolution amounts to a new breed of religious network. Southey next likens the emergent world order made possible by such technologies to the cosmic ambitions of Kehama, his own Indian tyrant-cum-demigod. The Colloquies thus suggests an allegorical reading of The Curse of Kehama, whereby this tale of a king bent on cosmic rule simultaneously explores how technological and imperial networks intertwine. Accordingly, I draw from metaphor theory to read the earlier Kehama as a repository of veiled comparisons and displacements through which Southey glimpses the magnitude of the Industrial Revolution. Just as Indian wealth propels the techno-imperial enterprise described in the Colloquies, Kehama’s paganism supplies the raw discursive material through which Southey fashions a poetics of manufacturing. Read alongside the Colloquies, Kehama aestheticizes the connection between imperial and technological systems, expresses the imaginative significance of twinned manufacturing novelties—the steam engine and coke smelting—and concretizes the opaque moral and poetic properties attaching to industrial power by depicting it in reference to the minutiae of Hindu religion so far as Southey understood it.